A nonlinear viscoelasticity theory for nematic liquid crystal elastomers. (June 2022) - Wang, Zheliang; El Hajj Chehade, Ali; Govindjee, Sanjay; Nguyen, Thao D.
Abstract: Liquid crystal elastomers (LCE) are elastomeric networks with mesogen moieties that can reorient and order in response to thermomechanical loads. Experiments have shown that the stress response of nematic LCEs is rate-dependent and exhibits large hysteresis upon load–unload. In this work, we developed a theory for the large deformation viscoelastic behavior of monodomain nematic elastomers that separately incorporates the hypothesized dissipation mechanisms of viscous mesogen rotation and viscoelastic network deformation. The theory is specialized to the case of a homogeneous director field and applied to investigate the contributions of the viscous director rotation and network deformation mechanisms in the case of the uniaxial stress response of monodomain materials with director orientation parallel and perpendicular to the loading axis.